Ball Milling Process Of Hydroxyapatite From Sea Shells By Synthesis Method With Low Temperature Hydrothermal - Rahmad Rasyidin; Ahmad Fadli; Silvia Reni Renti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Ball milling of hydroxyapatite from sea shells has been successfully done by the low temperature hydrothermal method. The purpose of research is to determine the effect of time and number of ball mill in ball mill process to character of hydroxyapatite properties. Firstly,sea shells were calcined at 1000°C for 24 hours for producing CaO. And then 55.63 grams of (NH4)2HPO4was dissolved in 600 mL of distilled water and then 45.91 grams of CaO added into the solution until formed a slurry. Subsequently, the slurry was dried in an oven at 120°C for 15 hours. The drued slurry was then milled trough a ball milling process with variations of time of 1, 2, and 4 hours and variations in number of 10, 20, and 30 grinding balls then calcined temperature 900°C holding time of 2 hours. The results showed that the smallest diameter of the crystal at the ball mill process for 2 hours using 20 grinding balls is 67 nm. While the surface area obtained will increase if the resulting smaller size of the crystal.Keywords: Ball mill, Hydroxyapatite, Hydrothermal, Sea Shells and Crystal Diameter